STUDY ON THE PROBLEM SOCIAL COMPETENCE AS A COMPONENT OF COMMUNICATIVE COMPETENCE - Brimzhanova, K.S.; Ivanova, Е.N.; Amirkhamzina, Zh.А. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
This article reveals the essence of the concept of "socio-cultural competence 'as one of the components of communicative competence, as a body of knowledge about the target language country, national and cultural features of the social and verbal behavior of native speakers and the ability to properly use these knowledge and skills in the process of verbal interaction, respecting the customs and traditions, rules of conduct, etiquette rules, taking into account the social conditions and behavior patterns of native speakers. The different interpretations of the concept of "socio-cultural competence". The structure of social competence in scientific research. The importance of the formation of competence in the work of many researchers, since the development of social competence plays a special role in the modern world, where there is rarely exacerbated inter-ethnic relations. The socio-cultural competence involves a willingness and ability to live and interact in today's multicultural world.
Keywords: communicative competence; sociocultural competence; formation; cross-cultural communication